Tricking Landau–Yang: How to obtain the diphoton excess from a vector resonance - Mikael Chala; Michael Duerr; Felix Kahlhoefer; Kai Schmidt-Hoberg (Physics Letters B, 2016)
We show that contrary to naive expectations the recently observed diphoton excess can be explained by a vector resonance, which decays to a photon and a light scalar s, followed by a decay of the scalar into two photons: Z′→γs→3γ. As the two photons from the scalar decay are highly boosted, the experimental signature is an apparent diphoton final state. In fact all the necessary ingredients are naturally present in Z′ models: Additional fermions with electroweak quantum numbers are required in order to render the theory anomaly free and naturally induce the required effective couplings, while the hidden Higgs which gives mass to the Z′ can be very light. In particular no new coloured states are required in this framework. We also show that in such a setup the width of the resonance can be rather large, while all couplings remain perturbative. Keywords: Mostly weak interactions: beyond standard model